The collisional depolarization of OH(A ²Σ⁺) and NO(A ²Σ⁺) with Kr - Chadwick, H; Brouard, M; Chang, Y; Eyles, C; McCrudden, G; Perkins, T; Seamons, SA; Kłos, J; Alexander, M; Dagdigian, P; Herráez-Aguilar, D; Aoiz, F (American Institute of Physics Inc., 2014)
Quantum beat spectroscopy has been used to measure rate coefficients at 300 K for collisional depolarization for NO(A 2Σ+) and OH(A 2Σ+) with krypton. Elastic depolarization rate coefficients have also been determined for OH(A) + Kr, and shown to make a much more significant contribution to the total depolarization rate than for NO(A) + Kr. While the experimental data for NO(A) + Kr are in excellent agreement with single surface quasiclassical trajectory (QCT) calculations carried out on the upper 2A ′ potential energy surface, the equivalent QCT and quantum mechanical calculations cannot account for the experimental results for OH(A) + Kr collisions, particularly at low N. This disagreement is due to the presence of competing electronic quenching at low N, which requires a multi-surface, non-adiabatic treatment. Somewhat improved agreement with experiment is obtained by means of trajectory surface hopping calculations that include non-adiabatic coupling between the ground 1A ′ and excited 2A ′ states of OH(X/A) + Kr, although the theoretical depolarization cross sections still significantly overestimate those obtained experimentally.